SINGLE PHOTON BONE DENSITOMETRY IN HEMODIALYSIS PATIENTS - Jaros, Antonin; Zadrazil, Josef; Konecny, Karel; Kosatikova, Zdena; Zahalkova, Jana; Vrublovsky, Petr; Krejci, Karel (Biomedical papers, 1999)
Renal osteodystrophy is a common finding in patients with renal insufficiency. The maximum of its intensity isfound in hemodialysis patients. Bone densitometry is so far the best method for non-invasive assessment of theextent of the illness. Some densitometric studies in hemodialysis patients have already been published but theirresults differ in prevalence and intensity of renal osteodystrophy. They also demonstrated a slight relationshipbetween intensity of renal osteodystrophy and duration of the dialysis treatment. Opinions vary on the relationshipbetween bone mineral density and markers of bone turnover. This cross-sectional study found high prevalence ofrenal osteodystrophy (Z-score below -1 in 57% of patients) as well as high a number of severely damaged patients(T-score below -2.5 in 40% of patients). It also showed some correlation between bone demineralisation and theduration of dialysis. None from evaluated markers of bone turnover correlated with bone mineral density.
Keywords: Bone densitometry/ Hemodialysis/ Renal osteodystrophy